Introduction - Laurie Edson (Studies in 20th & 21st Century Literature, 1993)
Introduction to the special issue
Keywords: contemporary feminist writing; feminist writers; French feminist writers; French-speaking writers; Sub-Saharan Africa; Maghreb; Caribbean; Canada; France; women writers; women; gender; gender issues; race; class; culture